Accomplishments of Heinz Baumberger PhD: a remarkable patient with ankylosing spondylitis for 72 years. Issue 6 (June 2016) - Khan, Muhammad
Abstract This is the story of a remarkable Swiss patient—Heinz Baumberger, PhD—who was born in 1931 and has suffered from ankylosing spondylitis (AS) since 1943. He has survived many manifestations and co-morbid conditions associated with his disease and its treatment. These include severe episodes of acute anterior uveitis, osteoporosis with fragility fractures, and also post-traumatic spinal fractures on three different occasions. In addition, he has suffered from multiple basal cell carcinomas as a late complication of a 3-week course of spinal radiation in 1952 and another one in 1962. It was only in 1971 that Dr. Baumberger for the first time met a fellow sufferer from AS, and he subsequently helped establish the Swiss AS patient support group, the second such national group in the world. He co-authored with his rheumatologist an excellent and well-illustrated book on AS for patients and their family members and for allied healthcare professionals. He travelled extensively around the globe lecturing and participating in various meetings and congresses in his zeal to spread the idea of self-help organizations for patients with AS.